What Can Welfare Stigma Do? - Whelan, Joe; Bolton, Robert; Dukelow, Fiona (My University, 2022)
In this ‘state of the art’ review, we draw on the Irish and UK context to ask ‘what can welfare stigma do?’ Our question provokes thinking about welfare stigma not as an inevitable ‘cost’ of the structure of welfare provision, but as something that does sociopolitical work and which may be deliberately mobilised to do so. This, we argue, is a particularly pertinent question to ask in the Irish and UK contexts, bound together by some shared liberal welfare regime characteristics that are particularly associated with welfare stigma and by the effects of a period of austerity capitalism that continues to re-shape the meaning and experience of welfare. Yet, going beyond welfare stigma as inherently negative, we highlight a limited literature on resistance that suggests the potentialities of welfare stigma in the service of positive social change toward a new welfare imaginary.
Keywords: Welfare stigma; resistance; Ireland; UK; Austerity capitalism.; Inclusive Society; Politics of the welfare state; SOCIAL POLICY; STIGMA; Social Welfare; Social policy analysis; Welfare State; Advocacy and political participation; Employment; Policy; Poverty; Social exclusion; Social participation; Social services, interventions and supports